PENGARUH PERILAKU DOUCHING TERHADAP KEJADIAN KANKER LEHER RAHIM DI RSD dr. SOEBANDI JEMBER - Wati, Dwi Martiana; Prasetyowati, Irma; Wulandari, Anisa Yulia (FKM - UNEJ, 2011)
Cervical cancer still become the first killer for women in growth countries, include Indonesia. The prevalence of cervical cancer in growth countries reached 77%. One of the risk factorÂ entrenched in modern women, is douching. The aim of this research was to analyze the effect of douching to cervical cancer incidence in dr. Soebandi regional hospital in Jember. This is an observational analitical research that use case-control approach. The statistical test used in this research was logistic regression with 5% significance level. There was significant effect of douching toward cervical cancer incidence, which the risk factor of a woman with douching to have cervical cancer four times greater than a woman who didnât do douching. Â Key words: douching, cervical cancer